Pengaruh Pemberian Tepung Ikan Lemuru (Sardenella Fimbriata) Terhadap Persentase Karkas Broiler - Sulaiman Ibrahim (Agricultural Faculty, 2007)
ABSTRACT. An experiment was conducted for five weeks to study the effect on feeding different levels of fish meal, Sarninella fibriata on carcass percentage of Cobb broiler strain. 120 day old Cobb chicks were randomly divided into eight expremiental groups, each consisting of 15 birds. Each groubs of 15 bird was divided into three replications of five birs, which then placed into 1x1 x 0.7 m cages at the rate of five birds per cage. Group one, two, three and four were fed 1 %, 4%, 7% and 10% of fish meal, Sardinella fibriata. Groub five, six, seven and eight were maintained with feed and water always available. The carcass percentage of teo birds of each five bird of each reflication were recorded at the end of the experiment. The average of carcass pecentage of groub one, two, three and four of fish meal. Sardinella fimbriata were 62, 67, 69, 68.40 and 69.37% resvectivaly. The average of carcass percentage of groub five, six, seven and eight of commercial fish meal were 63.22, 59.49, 64.90 and 70.22% respectively. There were significant different (P0.01) between groub six and groub eight of commercial fish meal, but there were no significant differences noted.